THE EFFECT OF SPRAYING OF BORON AND CARBO LIZER ON THE PRODUCTIVITY AND QUALITY OF DRY COWPEA SEEDS - & Albayati, Hanshal (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was carried out at the vegetable fields of Horticulture and Landscaping Design Dep. / College of Agriculture / university of Baghdad / Abu Ghraib on season  2014   to study the effect of spraying boron and Carbo lizer on the productivity and quality of cowpea seeds. Ramshorn c.v. Seeds are sowed on two dates; Spring and summer date. The experiment also includes the use of four concentrations of Boron: 0, 50, 100 and 200 mg. L-1 Which Symbolized B1,B2,B3 and B4 and three concentrations of Carbo lizer; 0, 1.25 and 2.5 cm3.L-1 Which Symbolized C1,C2 and C3. The experiment analysis is carried out in accordance to the experimental with in Randomized complete block design (RCBD) and it is adopted in three replacements, and it is compared with L.S.D. at 0.05 probability level. The results showed superiority of treatment B1 in yield of dry seeds 46.2 g.plant-1, percentage of carbohydrates 64.52% and the treatment B2 showed a significant increase in the bulk density of the seeds 0.669 g.cm3 , percentage of protein in the seeds 22.76% in the spring date while treatment B3 show a significant increase in the number of Seeds in pods 8.86 seed.pod-1, yield of dry seeds 99.8 g.plant-1, specific density 1.068 g.cm3 ,bulk density 0.698 g.cm3 and percentage of protein in the dry seeds 22:56% in the summer date, and excelled treatment of Carbo lizer C1 show a significant increase in yield of dry seeds 45.1 , 90.9 g.plant-1 for both dates respectivelly, The interaction treatment B1C1 show a significant increase in the number of seeds in pod 9.87 seed.pod-1 and yield of dry seeds g.plant-1 59.7 g.plant-1 in the spring date, while the interaction treatment was significantly B3C2 showed a significant increase in the number of seeds in pod 9.27 seed.pod-1 and percentage of protein 22.73% and The interaction treatment B3C1 show a significant increase yield of dry seeds 109.7 g.plant-1  bulk density 0.703 g.cm3 in the summer date, The interaction treatment B1C0 show a significant increase in percentage of carbohydrates 64.70 and 64.80% for both dates respectively.